Thermal diffusivity measurement of Zn, Ba, V, Y and Sn doped Bi-Pb-Sr-Ca-Cu-O ceramics superconductors by photoacoustic technique - M. Yunus, W. M.; Fanny, C. Y. J.; Phing, T. E.; Mohamed, S. B.; Halim, S. A.; Moksin, M. M. (Kluwer Academic Publishers, 2002)
The simple open photoacoustic cell technique is demonstrated for measuring the thermal diffusivity of the Zn, Ba, V, Y and Sn doped Bi-Pb-Sr-Ca-Cu-O superconducting ceramic samples. It is based upon the measurement of the photoacoustic signal as a function of the modulation frequency in the region where the sample thickness, ls, equal to the thermal diffusion length of the sample, μs. The obtained thermal diffusivity values of Ba, V, Y and Sn doped in Bi-Pb-Sr-Ca-Cu-O system increase with the increasing dopant concentration at Ca side. However, the thermal diffusivity values of Zn doped sample decrease with the increasing of dopant concentration in the system. The measured thermal diffusivity value was found to be very dependent on the dopant atom and dopant concentration.